Looking Back and Ahead: A Social Network Perspective on Workplace Learning and Professional Development - Van Waes Sara; Hytönen Kaisa (Springer, 2023)
In this chapter, we set forward a social network perspective on professional learning and development. The chapter stresses that how individuals learn and develop in and around the workplace is significantly affected by the way they are tied into a larger web of social connections. We reflect on the added value of a social network perspective to workplace learning research. Building on exemplary findings of recent studies, it shows that the pattern and quality of social relationships among professionals may significantly enhance our understanding of the ways in which interaction takes place and contributes to learning and development. We discuss how a social network approach allows to capture professional interactions in a more straightforward, visual and fine-grained way; and how it can simultaneously capture professional interactions at different levels of analysis (e.g., individuals, teams, units, organizations). We conclude by looking forward and setting up several avenues for future research.
Research Approaches on Workplace Learning: Insights from a Growing Field